ANALYSIS OF THE CAESAREAN SECTION ACCORDING TO ROBSON CLASSIFICATION AT RSUD PANEMBAHAN SENOPATI BANTUL IN 2021–2022 - Gumilar, Gulam; Emilia, Ova; E.S, Diannisa Ikarumi; Nurdiati, Detty (JURNAL KESEHATAN REPRODUKSI, 2024)
Background : The Robson 10-group classification system categorizes pregnant women into ten distinct groups based on specific obstetric characteristics. As caesarean section rates rise globally, this trend has become an important public health concern. Between 2012 and 2015, RSUD Panembahan Senopati Bantul, a regional government hospital in Indonesia, reported caesarean section rates exceeding 30%. The aim of this study is to identify which Robson groups contributed most to the significant increase in cesarean deliveries.Objective : This study aims to determine the rate of change in the trend of caesarean section rates that occurred at Bantul Regional General Hospital during the 2021–2022 period using the Robson Classification.Methods : This study used a descriptive analytic design. The study population included all pregnant women who gave birth at RSUD Panembahan Senopati in Bantul from 2021 to 2022. Data were obtained from secondary sources using Case Report Form (CRF) instruments and processed using Robson classification. Additional analyses were conducted to determine the cesarean section rate within each group and identify reasons for cesarean delivery.Results  : Of the 2,295 study participants, 906 (39.8%, 95% CI 38.27–41.33) were pregnant women who delivered by C-section during 2021–2022. The C-section rate declined by 1.53% overall over the two-year period (95% CI 1.08–2.12). However, several Robson groups showed rising C-section trends. According to the Robson classification, group 5 represented the largest proportion of the population (25.1%, 95% confidence interval [CI] 23.09–27.12) and accounted for the highest proportion of cesarean deliveries (9.9%), followed by group 4 (6.2%, 95% CI 3.22–8.27). Groups 2, 4, and 7 experienced rising C-section trends from 2021 to 2022, with Group 4 showing the greatest increase (8.5%), followed by Group 2 (4.4%, 95% CI 1.2–6.75). Further evaluation identified failed labor induction as the leading cause of the increased C-section rate (14.6%, 95% CI 12.02–17.9), while fetal compromise/distress also played a significant role (10.6%, 95% CI 8.79–12.5).Conclusion : From 2021 to 2022, the caesarean section rate at RSUD Panembahan Senopati Bantul decreased by 1.53% (95% CI 1.08–2.12), though certain groups still had elevated rates. Groups 2, 4, and 5 accounted for the majority of cesarean deliveries during this period. Targeted interventions, including routine evaluations and improved management, are needed to reduce the overall C-section rate further.